2016
DOI: 10.1371/journal.pone.0166523
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Map of the Healthy Equine Gastrointestinal Tract

Abstract: Horses are exquisitely sensitive to non-specific gastrointestinal disturbances as well as systemic and extraintestinal conditions related to gut health, yet minimal data are available regarding the composition of the microbiota present in the equine stomach, small intestine, and cecum and their relation to fecal microbiota. Moreover, there is minimal information regarding the concordance of the luminal and mucosal microbial communities throughout the equine gut. Illumina-based 16S rRNA gene amplicon sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
88
1
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 38 publications
(49 reference statements)
14
88
1
20
Order By: Relevance
“…First, we explored the perinatal bacterial colonisation events of the foal gut and the phylogenetic structure of the microbial ecosystems from meconium, amniotic fluid and mare faeces were characterised and compared. In agreement with previous studies [11,12,29], the core community of the mare gut showed the characteristic compositional layout of a fibrolytic and short-chain fatty acid-producing mutualistic microbiome, being enriched in Clostridiales, Lachnospiraceae and Ruminococcaceae. Conversely, the phylogenetic layout of the microbial communities from meconium and amniotic fluid shared a peculiar ecological structure, including OTUs from ubiquitous microorganisms and components from mare microbiomes at subdominant, but still relevant percentages.…”
Section: Discussionsupporting
confidence: 91%
“…First, we explored the perinatal bacterial colonisation events of the foal gut and the phylogenetic structure of the microbial ecosystems from meconium, amniotic fluid and mare faeces were characterised and compared. In agreement with previous studies [11,12,29], the core community of the mare gut showed the characteristic compositional layout of a fibrolytic and short-chain fatty acid-producing mutualistic microbiome, being enriched in Clostridiales, Lachnospiraceae and Ruminococcaceae. Conversely, the phylogenetic layout of the microbial communities from meconium and amniotic fluid shared a peculiar ecological structure, including OTUs from ubiquitous microorganisms and components from mare microbiomes at subdominant, but still relevant percentages.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the current study, Firmicutes (44%) and Bacteroidetes (38%) together comprised more than 90% of total bacterial abundance. The ratio of Firmicutes to Bacteroidetes ranged from 1:1 to greater than 4:1 in the gut microbiota of healthy horses. Some of these discrepancies in the relative abundance of bacterial populations are associated with the variation in the unclassified sequences reported in literature, for example Shepherd et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although highly variable between horses, Ericsson et al [25] reported an abundance of α- Proteobacteria in the upper gastrointestinal tract of 9 healthy horses. No information is available on what the horses were fed pre-euthanasia, but it is conceivable that like the forages in this study, Proteobacteria was present in significant numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The highly individualistic nature of the gut microbiome noted by both 25. Ericsson et al [25] and Dougal et al, [22,23], and the multiple small OTU core suggests that the gastric profile may lack robustness and be easily influenced by external factors. Understanding how the gastric microbiome responds to the epiphytic challenge from fodder may provide additional insight into gastric pathologies such as ulceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation